Thermodynamic Properties of Water Adsorption on Gaplek Flour Fortified with Red Bead Tree Seed - Margareta Novian Cahyanti; Alvama Pattiserlihun (Molekul, 2018)
The moisture sorption isotherm data of gaplek flour fortified with red bead tree seed stored in a chamber, the relative humidity of chamber ranging from 10% to 97% regulated using a saturated salt solution, was determined at three temperatures 25°, 35°, and 45 °C. The experimental data used to determine the thermodynamic functions were isosteric heat of sorption, sorption entropy, and free energy changes. The sorption isosteric heats were determined by the application of the Clausius–Clapeyron equation. Isosteric heats of adsorption increased to maximum level and then declined with increase of moisture content. Adsorption entropy increased to maximum level and then declined with the increase of moisture content. The free energy changes increased with increase in moisture content. The spreading pressure increased with increasing water activity.